Magnetisation transfer parameters and stroke outcome. Issue 6 (June 2015) - Sibon, I.; Tourdias, T.; Felix, S.; Asselineau, J.; Bracoud, L.; Vivot, A.; Rouanet, F.; Renou, P.; Orgogozo, J.M.; Dousset, V.
Abstract Our aim was to evaluate the association between magnetisation transfer imaging (MTI) parameters measured 30 to 45 days after a cerebrovascular insult and post-stroke functional outcome at the same time. MTI offers the opportunity to depict subtle microstructural changes in infarcted areas. The clinical significance of the heterogeneity of brain damage within ischaemic stroke lesions is unknown. We prospectively included 58 patients with acute middle cerebral artery stroke. Diffusion-weighted imaging was performed within 12 hours after onset and the final infarct was documented by MRI with fluid-attenuated inversion recovery (FLAIR) and MTI at 30 to 45 days follow-up. We evaluated the association between MTI histogram parameters and the clinical outcome assessed by dichotomised (threshold >2) modified rankin scale (mRS) using multivariable logistic regression models adjusted on baseline characteristics. In multivariable analyses, stroke outcome was mostly driven by initial National Institutes of Health Stroke Scale (odds ratio [OR] = 1.23; 95% confidence interval [CI] = 1.07–1.41; p < 0.01) while after adjustment of initial stroke severity magnetisation transfer ratio peak position was the only MRI parameter associated with functional status at 30 to 45 days post-stroke (OR = 0.86; 95% CI = 0.75–0.98; p = 0.02); lower peak position values associated with higher mRS. Conversely, stroke volume measured on FLAIR sequence was not associated with stroke prognosis (p = 0.87). The intensity of microstructural changes within the infarct core measured at 30 to 45 days follow-up is independently associated with the functional status evaluated at the same time. MTI and related parameters could be used as surrogate markers of treatment response in stroke clinical trials.